2021
DOI: 10.1021/acsami.1c10765
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Chemistry of Polydimethylsiloxane Foam in Radiation-Thermal Environments: Experiments and Simulations

Abstract: The γ radiolysis behavior of polydimethylsiloxane (PDMS) in the radiation-thermal environments (dose rate, 0.2 Gy/s) is studied to pinpoint the basic knowledge of the temperature (20–70 °C) effects. The non-monotonous temperature effects on the formation of gas products, paramagnetic species in silica, and cross-linking density are proposed to correlate with the complex chemical reaction mechanisms. Besides, molecular dynamics simulation and theoretical calculation are first performed simultaneously based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 59 publications
(150 reference statements)
5
57
0
Order By: Relevance
“…In recent years, molecular dynamics (MD) simulation has been employed as an effective theoretical tool to comprehend quantitatively the structure-performance relationships of polymer materials at the molecular scale, especially in modification of polymers and diffusion of small molecules in polymers [28,29]. Although the molecular dynamics simulation methods were preliminarily applied to estimate the thermal oxidative aging mechanism of rubber materials [30][31][32], the chemical reactions such as oxidation products during the aging process are not fully considered by researchers. For example, Wang et al [30] found that rubber at low compressive strain possesses high fractional free volume, molecular chain movement, and ozone permeability by molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular dynamics (MD) simulation has been employed as an effective theoretical tool to comprehend quantitatively the structure-performance relationships of polymer materials at the molecular scale, especially in modification of polymers and diffusion of small molecules in polymers [28,29]. Although the molecular dynamics simulation methods were preliminarily applied to estimate the thermal oxidative aging mechanism of rubber materials [30][31][32], the chemical reactions such as oxidation products during the aging process are not fully considered by researchers. For example, Wang et al [30] found that rubber at low compressive strain possesses high fractional free volume, molecular chain movement, and ozone permeability by molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Common vectors for degradation arise from the ready uptake of environmental water [4][5][6][7] or absorption of radiation. [7][8][9][10][11][12] Understanding the degradation responses of PDMS has enormous practical applications, ranging from assessing environmental impacts [13][14][15] to establishing models for the aging and lifetime prediction of silicone components. [4][5][6][7][8][9][10][11][12]16,17 Ionizing radiation is a common cause for polymer degradation that can arise during component sterilization, 1,18,19 as a consequence of planned operation conditions, and as a driver in accelerated aging studies.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Understanding the degradation responses of PDMS has enormous practical applications, ranging from assessing environmental impacts [13][14][15] to establishing models for the aging and lifetime prediction of silicone components. [4][5][6][7][8][9][10][11][12]16,17 Ionizing radiation is a common cause for polymer degradation that can arise during component sterilization, 1,18,19 as a consequence of planned operation conditions, and as a driver in accelerated aging studies. [7][8][9][10][11][12] In 1955, Charlesby proposed 20 a set of reaction schemes for crosslinking in irradiated PDMS that were quickly refined by others 21,22 and were based on IR vibrational spectroscopy, titration, mass spectra of off-gassing species, and chromatography (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations